The New Lease Accountung Model and its Consequenses - Kuzior, Anna (Studia Oeconomica Posnaniensia, 2016)
The article presents basic assumptions concerning lessee accounting presenting in IFRS 16 Leases. The standard was issued in January 2016, and is effective for the annual reporting period beginning after 1 January 2019. The IASB presented the single lessee accounting model. All lease contracts will be presented in a statement of financial position as the right of use asset and lease liabilities. The right of use asset will be depreciated; liabilities will be measured at an amortized cost using the effective interest method. The new accounting model for lessee will result in increase of assets and liabilities recognized in financial statements. It also will be different than operating leases, a structure of expenses influencing net profit. In consequence, basic financial ratios will change. The introduced single model for lessee, especially presentation liabilities in statement of financial positions, will increase the quality of financial reporting.